Nurse-Led Telehealth Oncology Clinic on ‘Home Management During Chemotherapy’ for Gastrointestinal Cancer Patients: Study Protocol of A Mixed Method Study - Ahwal, Sarita; Rai, Kanika; Jindal, Ankur; Sahai, Puja (National Journal of Community Medicine, 2024)
Introduction: Telehealth is increasingly being used for symptom management among cancer patients on chemotherapy. Objective of the study is to develop Nurse-led Tele-health Oncology Clinic for GI cancer patients regarding ‘Home Management during Chemotherapy’. Methods: The study will follow sequential explanatory mixed method design where during quantitative phase, using RCT (CTRI/2024/01/062028), GI cancer patients of age 18-65 years and undergoing 2nd or 3rd chemotherapy cycle will be randomised after obtaining consent to experimental (EG) & control (CG) groups. Ethical Clearance is already obtained. EG will be followed through Nurse-led Clinic which includes multiple virtual educational & counselling sessions, e-booklet on side effects management, PMRT, Support groups & telephonic follow ups. Effectiveness will be measured in terms of Quality of life, severity of side effects and Anxiety using FACT-G, CTCAE and DASS respectively. In qualitative phase, using extreme case sampling, in-depth interviews from consented participants will be conducted to explore experiences towards intervention. Analysis: Analysis of quantitative data will use descriptive and inferential statistics. This follows thematic analysis and integration of data. Conclusion: The study protocol will provide guidance to optimize utility of tele-medicine technology to improve healthcare outcomes especially for the GI cancer patients.